El trabajo en grupo de las secretarias dentro del gobierno autónomo descentralizado municipal del cantón Latacunga para mejorar el trato a los clientes y personal que labora en la institución - Chicaiza Chicaiza, Sandra Marina (2015)
Decentralized Autonomous Municipal Government of Latacunga Canton is located in the street Fernando Sanchez de Orellana and General Maldonado, opposite the park Vicente Leon; it is an institution that seeks the welfare of all citizens in different aspects both in rural and urban part, fulfilling all his actions fully and excellence. The strategic plan has been designed with the purpose of creating strategies for secretarial staff Decentralized Autonomous Municipal Government of Latacunga Canton through group work, the main base of the institution, who have contact with customers and staff entity, with the aim of improving customer service, good communication and secretarial complying with different activities, thereby obtaining excellent and accurate in providing good service to the public results. The most important strategies that will help us work together are communication, motivation, collaboration, among others, will bring with it a knowledge that will serve the development of various actions and therefore know how important it is to work in groups….